Program Eco-Pesantren Sebagai Pendidikan Ramah Lingkungan Dalam Pengelolaan Lingkungan Hidup - Ma'rufabadi (Mujalasat: Multidiciplinary Journal of Islamic Studies, 2024)
The focus of this research is to explore the implementation of environmentally conscious education based on pesantren (eco-pesantren), a combination of scientific and religious knowledge. It is expected that eco-pesantren-based education can cultivate students' awareness of the environment. This research is conducted at Daarul Ma’rifat Islamic Boarding School in North Lampung. It is a qualitative study using a case study model, employing data collection techniques such as interviews, observations, and documentation. The results of this research indicate the students' interest in participating in the program. Furthermore, the program has successfully instilled environmental responsibility awareness in the students.